Pengaruh Penggunaan Smartphone, Manajemen Waktu, dan Motivasi Belajar Terhadap Hasil Belajar Mata Pelajaran Ekonomi Siswa Kelas XI Di SMA Negeri 3 Pinrang - Rahma; Muhammad Azis; Nuraisyiah (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
The purpose of this study was to examine the effect of smartphone use, time management, and learning motivation on the economics learning outcomes of grade XI students of SMA Negeri 3 Pinrang. The proportional stratified random sampling technique used resulted in 48 samples which were then surveyed with a questionnaire. The results showed that smartphone use, time management, and learning motivation in partial and simultaneous terms had a good and real influence on the economics learning outcomes of grade XI students of SMA Negeri 3 Pinrang, and the learning motivation variable had a controlling influence on learning outcomes.